Intentional self-harm associated mortality among U.S. White physicians, nurses, lawyers & judges - Gupta, Deepak; Kumar, Sarwan; Chakrabortty, Shushovan (Indian Journal of Community Health, 2020)
The mortality associated factors can be quantified in terms of proportionate mortality ratios (PMR) per National Occupational Mortality Surveillance (NOMS) data. Therefore, we explored NOMS data for the United States (U.S.) occupational workers’ mortality during 1999, 2003-2004, 2007-2014 to compare physicians’ mortality associated factors to the mortality associated factors among nurses vs. the mortality associated factors among lawyers & judges. Due to lack of adequate sample sizes of decedents being concurrently present among physicians, nurses, and lawyers & judges of Black race, we were able to tabulate 25 causes of death with significant PMRs among physicians, nurses, and lawyers & judges only of White race. Therein, intentional self harm associated mortality was found to be common among U.S. White physicians, nurses, lawyers & judges.